2002
DOI: 10.1046/j.1469-8137.2003.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite transport into paddy rice (Oryza sativa) roots

Abstract: Summary• Here the mechanism of arsenite transport into paddy rice ( Oryza sativa ) roots, uptake of which is described by Michaelis-Menten kinetics, is reported. A recent study on yeast ( Saccharomyces cerevisiae ) showed that undissociated arsenite (its pK a is 9.2) was transported across the plasma membrane via a glycerol transporting channel. To investigate whether the same mechanism of transport was involved for rice, competitive studies with glycerol, which is transported into cells via aquaporins, were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(161 citation statements)
references
References 21 publications
7
150
0
4
Order By: Relevance
“…Our findings showed that glycerol and Ag þ did not compete with OTC for uptake and transport into alfalfa roots, suggesting that OTC does not enter into the root through water channels. The glycerol concentration of 10 mM used in the present study was high enough to inhibit arsenite uptake by rice within 20 min, which is sufficient for the inhibition of aquaporins (Meharg and Jardine, 2003), and the 5 mM of Ag þ was also suitable (Niemietz and Tyerman, 2002). Therefore, our data convincingly demonstrated that OTC uptake was aquaporins-independent.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our findings showed that glycerol and Ag þ did not compete with OTC for uptake and transport into alfalfa roots, suggesting that OTC does not enter into the root through water channels. The glycerol concentration of 10 mM used in the present study was high enough to inhibit arsenite uptake by rice within 20 min, which is sufficient for the inhibition of aquaporins (Meharg and Jardine, 2003), and the 5 mM of Ag þ was also suitable (Niemietz and Tyerman, 2002). Therefore, our data convincingly demonstrated that OTC uptake was aquaporins-independent.…”
Section: Discussionsupporting
confidence: 71%
“…OTC uptake by alfalfa roots was decreased when exposed to 0.01 and 0.1 mM Hg 2þ compared with the control (Table 1). However, the reduction in OTC uptake after the addition of Hg 2þ could be due to general disruption of plasma membrane biochemistry caused by the highly toxic Hg 2þ ion (Dordas and Brown, 2001;Martre et al, 2001;Du et al, 2005), rather than specific inhibition of aquaporins (Meharg and Jardine, 2003). To further elucidate the possible role of aquaporins in OTC uptake, we used the other competitors, such as glycerol and Ag þ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of Si to the pretreatment or uptake solution significantly decreased shoot and root As concentrations, suggesting that both external and internal Si could affect As uptake. The kinetics study showed that in the treatment without Si the uptake kinetics were similar to those obtained by Meharg and Jardine (2003) and Chen et al (2005). Uptake of As by rice roots was significantly influenced by ÀSi þ Si treatment (Table 3).…”
Section: Discussionsupporting
confidence: 68%
“…Roots were excised and incubated in deionized water for 20 min at room temperature and were then transferred to conical flasks containing 1000 ml test solution, and incubated for further 30 min according to Meharg and Jardine (2003) and Chen et al (2005). The test solutions with different concentrations of As were 1.5, 3.0, 7.5, 15.0, 30.0 and 75.0 mM.…”
Section: Experiments Ii: Effects Of Si Treatments On Kinetics Of Arsenmentioning
confidence: 99%